2018
DOI: 10.1093/jxb/ery139
|View full text |Cite
|
Sign up to set email alerts
|

ECD1 functions as an RNA-editing trans-factor of rps14-149 in plastids and is required for early chloroplast development in seedlings

Abstract: The pentatricopeptide repeat protein ECD1 functions as an RNA-editing trans-factor in plastids of cotyledons and is necessary for early chloroplast development in Arabidopsis seedlings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…With a different genetic approach based on a different mutant allele of the EMB2261 gene, we confirm the conclusion of Jiang et al (2018) , claiming that EMB2261/ECD1 is the editing specificity factor of rps14-2 in Arabidopsis chloroplasts and is essential for Arabidopsis development. Here, we discuss the implication of this finding from four aspects: (1) editing factor mutants as surrogate mutants of the corresponding genes; (2) PPR specificity factors as limiting factors in RNA editing; (3) editing specificity determinants beyond the PPR-RNA recognition code; and (4) co-evolutionary scenarios involving PPR RNA editing factors and their targets.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…With a different genetic approach based on a different mutant allele of the EMB2261 gene, we confirm the conclusion of Jiang et al (2018) , claiming that EMB2261/ECD1 is the editing specificity factor of rps14-2 in Arabidopsis chloroplasts and is essential for Arabidopsis development. Here, we discuss the implication of this finding from four aspects: (1) editing factor mutants as surrogate mutants of the corresponding genes; (2) PPR specificity factors as limiting factors in RNA editing; (3) editing specificity determinants beyond the PPR-RNA recognition code; and (4) co-evolutionary scenarios involving PPR RNA editing factors and their targets.…”
Section: Discussionsupporting
confidence: 73%
“…During the writing up of this work, an independent manuscript reported that ECD1 (synonymous with EMB2261) is required for editing of the rps14-2 site in Arabidopsis and is required for early chloroplast development ( Jiang et al, 2018 ). We confirm this conclusion with a different genetic approach and a different mutant allele of the EMB2261 gene, and expand these findings by considering the specificity of the EMB2261/ rps14-2 interaction and the evolutionary history of the pair.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the increasing information about the subfamily classification and organellar targeting of PPR proteins in plants, the cellular role and function of most PPR proteins are still so far from fully being apprehended (Lee et al, 2019). Among these PPR proteins, several mutants show pigment defective or lethal phenotypes, such as sel1 (Pyo et al, 2013), ecd1 (Jiang et al, 2018), ppr4, emb2654 (Lee et al, 2019), and sot5/emb2279 (Huang et al, 2018) in addition to pdm2 and pdm3 mutants (Du et al, 2017; which have been reported in our lab before. These works suggest that most functional PPR proteins located in the chloroplast mainly play a critical role in accumulation of chlorophyll and are essential for plant survival.…”
Section: Discussionmentioning
confidence: 74%
“…Pentatricopeptide repeat (PPR) proteins form the largest family of proteins known to date that are directly involved in posttranscriptional modification in higher plants. Accumulating data indicate that PPR family members serve diverse functions in posttranscriptional modification, such as RNA editing (Ichinose & Sugita, 2018;Jiang et al, 2018;Xiao et al, 2018a,b), RNA splicing Huang et al, 2018;Tadini et al, 2018), RNA processing (Rackham et al, 2016;Stoll et al, 2017), RNA stability (Hammani et al, 2016;Zoschke et al, 2016;, RNA translation Legen et al, 2018), and RNA maturation (W. . The PPR gene family comprises 450 members in Arabidopsis and 477 members in rice (Saha et al, 2007;Barkan & Small, 2014).…”
Section: Introductionmentioning
confidence: 99%